Risk Management Framework for Social Enterprise: A Case of Vegetarian Restaurant - Maitri Purnama Sari; Didi Sundiman (Bina Nusantara University, 2019)
The purpose of this research was to find out the risks influenced the field of business for social enterprises, and how these risks affected the aspects of social enterprise. This research used a qualitative research approach. The data analyzed in this research were the results of questionnaires and interviews with 17 informants from the vegetarian restaurants in Batam. The results of the questionnaire were processed using Analytic Hierarchy Process (AHP) as analytical tools. This research used descriptive statistical analysis techniques as a data analysis. The results show that the risks examined in this research influence financial losses, image, growth, and quality of the organization. The intention and behavior risk has the highest effect, while financial risk is the lowest.